Evidence- based Policy and Decision-Making among Health Managers: A Case of Shiraz University of Medical Sciences - Bastani, Peivand; Kavosi, Zahra; Ali Poori, Somayeh; Imani Nasab, Mohammad Hassan (Galen Medical Journal, 2017)
Background: According to the importance of evidence-based policy-making in health scope, this study was conducted to investigate the present situation of decision-making among medical managers.Materials and Methods: This cross-sectional study carried out on all the managers worked in one of the hospitals, health centers, medical schools and central departments of Shiraz University of Medical Sciences in 2016. A questionnaire containing demographic data and 50 questions was applied to 5 sections: attitude (9), subjective norms (13), perceived controlled behavior (22), intention (3) and behavior (3). Choronbache α was between 0.73-0.91 emphasizing a good reliability, the questionnaire`s content and face validity were 0.83 and 0.67 respectively. Data was analyzed using Independent t-test, ANOVA, and Pearson correlation. Results: The greatest frequency of the respondents belongs to the men (77/85.1%), and the majority of the respondents were in an age range from 30 to 40 years. The highest mean score was related to the indirect attitude (8.17), and the lowest was obtained for the indirect perception (1.21). There was a statistical relationship between the mean score of direct and indirect controlled perceived behavior according to the participants’ educational level (P=0.03 and P=0.043, respectively). A significant relationship was also be observed between direct behavior and educational major (P=0.044). Pearson correlation indicates a significant positive relationship between the manager intention for evidence-based policy-making and all the other variables. Conclusion: It seems that the present situation of evidence-based decision-making is not appropriate for the university managers. In this regard, planning for the effective courses in knowledge translation, evidence-based policy-making and advanced searching along with monitoring the managers’ decision outcomes through an internal and external audit can have an effective role in improving decisions and enhancing evidence application. [GMJ.2017;6(1):30-38]